The role of trust in organization in the relationship between resistance to change and communication : The moderating effects of organizational justice and psychological capital on this relationship - Saruhan, Neşe (My University, 2013)
Kurumsal Değişim, Değişime Direnç, Kuruma Güven, Kurumsal Adalet, Psikolojik Sermaye ÖZET İLETİŞİMİN, KURUMA GÜVEN ARACILIĞIYLA DEĞİŞİME DİRENÇ İLE OLAN İLİŞKİSİNDE PSİKOLOJİK SERMAYE VE ALGILANAN KURUMSAL ADALETİN ŞARTLI DEĞİŞKEN ROLÜ Sürekli değişim içerisinde olan ekonomik ve pazar koşullarında, kurumlar rekabet üstünlüklerini korumak için stratejik, yapısal ve iş yapma şekilleri gibi farklı alanlarda değişim uygulamaları gerçekleştirmektedirler. Kotter ve Schlesinger’e (1978) göre pek çok kurum her yıl orta düzeyde bir değişim gerçekleştirirken, dört-beş yıl içerisinde rekabet koşulları, teknolojik gelişmeler, büyüme ve iş gücündeki değişimler çerçevesinde büyük ölçekli bir değişim gerçekleştirmelidir. Bu araştırmada kurumsal değişimlerin daha başarılı sonuçlar elde etmesi için çalışanların değişime gösterdiği tepkiler ve bu tepkileri etkileyen unsurlar incelenmiştir. Araştırma kapsamında değişime direnci etkileyen unsurlar olarak, kurum içerindeki iletişim, kuruma güven, algılanan kurumsal adalet, psikolojik sermaye, ele alınmıştır. Bu çalışmada, iletişimin kuruma güven aracılığıyla değişime direnç olan etkisi incelenmiştir. Ayrıca, psikolojik sermayenin, kuruma güven ile değişime direnç arasındaki şartlı değişen rolü ve algılanan örgütsel adaletin, iletişim ile kuruma güven arasındaki şartlı değişken rolü incelenmiştir. Bu çalışmaya farklı kurumlarda çalışan toplam 583 kişi katılmıştır. Analizlerin sonucunda kuruma güvenin iletişim ile değişime direnç arasında ara değişken rolü üstlendiği bulunmuştur. Diğer yandan, algılanan kurumsal adaletin iletişim ile kuruma güven arasında şartlı değişken rolü üstlenmediği bulunmuştur. Psikolojik sermayenin kuruma güven ile değişime direnç arasında şartlı değişken rolü üstlenmediği bulunmuştur. Organizational change, resistance to change, trust in organization, organizational justice, psychological capital

THE ROLE OF TRUST IN ORGANIZATION IN THE RELATIONSHIP BETWEEN RESISTANCE TO CHANGE AND COMMUNICATION. THE MODERATING EFFECTS OF ORGANIZATIONAL JUSTICE AND PSYCHOLOGICAL CAPITAL ON THIS RELATIONSHIP Due to dynamic business environments, organizations must implement changes in their strategies, structures and/ or processes when existing conditions are not sufficient to create a competitive advantage in the market. According to Kotter and Schlesinger (1978), most companies must undertake moderate organizational changes at least once a year and major changes every four or five years because of increasing demands from government, growth, competition, technological development, and changes in workforce. With all this movement, organizational change has become a very popular topic for scholars. In this research, factors affecting an individual’s response to organizational change were investigated in order to determine how organizational changes can be more successful. The contribution of communication on resistance to change through trust in organization was explored. Also, the moderating effect of perception of organizational justice on the relationship between communication and trust in organization and the moderating effect of psychological capital on the relationship between trust in organization and resistance to change were analyzed. The research was conducted among 583 employees. The results of the regression analysis showed that trust in organization plays a mediating role between communication to resistance and change. On the other hand, perception of organizational justice does not play a moderating role between communication and trust in organization. In addition, psychological capital does not play a moderating role between trust in organization and resistance to change.
Keywords: İşletme; Örgüt Kültürü; Örgütsel Davranış